Improved thermoelectric performance of flexible p-type SiGe films by B-doped Al-induced layer exchange. (12th December 2019) - Tsuji, M; Imajo, T; Saitoh, N; Yoshizawa, N; Suemasu, T; Toko, K
Abstract: The Al-induced layer exchange is a useful method for the low-temperature synthesis of high-performance SiGe thermoelectric thin films. Because B has a high solid solubility in SiGe, we examined the self-organized doping of B to SiGe during layer exchange to further improve p-type thermoelectric properties. The hole concentration and the electrical conductivity were improved in the whole SiGe composition range when an appropriate amount (~1%) of B to Al was added. A Si0.4 Ge0.6 layer fabricated on a polyimide substrate at 350 °C exhibited a power factor of 240 µ W m −1 K −2, which is best recorded as environmentally-friendly inorganic semiconductors formed on flexible substrates. The low-temperature Fermi-level-control technology for semiconductor films will exploit various flexible devices including thin-film thermoelectrics.